From cold case to gold case : how to craft engaging case films - Ampe, Peter, ....- (Gent : Borgerhoff & Lamberigts, 2020)
How to translate an idea into a compelling case study film. The author Peter Ampe combines fifteen years of jury experience with sharp analyses of award-winning cases. This guide is based on the vital insight that case study films have a lot in common with short movies. You will learn how to go from copywriter to screenwriter and use plot, genre and structure to evolve from complacent to compelling, from messy to seamless – from case to story. This step by step guide provides an essential tool for every advertising professional to make better case study films.
Keywords: Advertising ; cases; Marketing